Fragments d'un discours amoureux - Barthes, Roland 1915-1980 (Paris Éditions du Seuil, 1977)
'Fragments d’un discours amoureux' (A Lover's Discourse: Fragments) contains a list of "fragments", some of which come from literature and some from his own philosophical thought, of a lover's point of view. Barthes calls them "figures"—gestures of the lover at work.
Bibliography: p. 279-[281]
Keywords: Philosophy; Literature; Semantics; Emotion